New acoustic and molecular data shed light on the poorly known amazonian frog adenomera simonstuarti (Leptodactylidae): Implications for distribution and conservation - Carvalho, Thiago R. [UNESP]; Moraes, Leandro J. C. L.; Angulo, Ariadne; Werneck, Fernanda P.; Icochea, Javier; Lima, Albertina P. (Museum National D'Histoire Naturelle, 2020)
Adenomera simonstuarti is a poorly known species complex inhabiting western Amazonia. Here we reevaluate the species diversity within this complex based on previously documented and newly acquired molecular and phenotypic data. We also redescribe the calling pattern of the nominal species based on the original recording (Peru) and a new recording (Brazil). Our results indicate eight geographically structured genetic lineages and the nominal species with a multi-note call pattern. This is the first association of calls and DNA sequence from a voucher specimen, thereby enabling the assignment of A. simonstuarti to one specific lineage within the complex. The multi-note call was not previously reported and represents an important additional diagnostic character within Adenomera. The geographic distribution of A. simonstuarti is substantially narrowed down to the southwestern portion of the entire geographic range recognized for the complex. The lack of taxonomic resolution in the complex is a major conservation concern by preventing us from evaluating the potential threats and extinction risks of each of the lineages. Future research should follow the protocol of combining calls and DNA sequences associated with voucher specimens as a means to address the taxonomic status of genetic lineages within the A. simonstuarti complex.
Keywords: Acoustic diagnosis; Adenomera andreae clade; Amazon Basin; Cryptic diversity; Western Amazonia